2023
DOI: 10.1039/d3tb00536d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of graphenic surfaces by oxygen plasma toward enhanced wettability and cell adhesion: experiments corroborated by molecular modelling

Abstract: Graphenic materials attract huge attention because of their outstanding properties, showing wide applications as, i.a., components of biomaterials. Due to their hydrophobic nature, however, the surfaces need to be functionalized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…However, the presence of more polar groups (such as urea groups) with increasing R -values resulted in an increase in the surface polarity of the material and a slight decrease in the contact angle, in agreement with the FTIR-ATR split-peak data, which may be related to the increase in the number of polar groups on the surface. 48…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of more polar groups (such as urea groups) with increasing R -values resulted in an increase in the surface polarity of the material and a slight decrease in the contact angle, in agreement with the FTIR-ATR split-peak data, which may be related to the increase in the number of polar groups on the surface. 48…”
Section: Resultsmentioning
confidence: 99%
“…The greatest change in the intensity can be observed in the case of the long oxygen plasma pre-treatment. It can be concluded that oxygen plasma modification forms (among others) hydroxyl groups onto the surface [ 25 , 26 ], which subsequently react with HMDS vapors during the hydrophobization process. Kodaira et al [ 27 ] deposited HMDS films onto the glass plates using an atmospheric plasma torch from a mixture of HMDS, argon, and air.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of nanotechnology into medical research marks a significant advancement, especially in the development of innovative therapeutic strategies. This is particularly visible in the judicious integration of nanomaterials with biological mechanisms, which holds the promise of transforming the way diseases are treated at both the molecular and cellular scales. The use of two-dimensional (2D) carbon-based materials, such as graphene (G) and/or GO, is increasingly being explored in the context of treating a variety of ailments, including cancer, gastrointestinal infections, and neurodegenerative diseases, like AD and PD, etc. …”
Section: Introductionmentioning
confidence: 99%